Effects of Home-based Caregivers’ Stigma on Adherence to Arvs Among Hiv/aids Children at Mukono Church of Uganda Hospital - Lilian Namalishe (Uganda Christian University, 2024)
The stigma associated with HIV/AIDS remains a significant barrier to the adherence of ARVS among HIV-positive individuals. Home-based caregivers play a vital role in the management of Antiretroviral Therapy (ART) treatment among HIV children however the stigma associated with HIV/AIDS deeply influences their caregiving practices and health outcomes of their children. This study explored the impact of stigma experienced by home-based caregivers on the adherence to ARVS among HIV/AIDS children. The research was carried out at Mukono Church of Uganda Hospital which assessed how stigma affected the respondents’ ability to consistently administer antiretroviral therapy. The study employed a phenomenological design to understand the caregivers’ experiences, perceptions and emotions related to stigma and adherence. Both Qualitative and quantitative data was employed to offer a comprehensive understanding of the research problem. Data collection entailed self-administered questionnaires and interviews allowing direct insights from a total of 60 caregivers. This study focused on various dimensions of stigma which included internalized, perceived and public stigma. The findings indicate that caregiver’s stigma impairs adherence by affecting their motivation and capacity to manage the regimen treatment for their HIV/AIDS children. Stigma contributes to feelings of shame, isolation and fears of discrimination hence these finding highlight the need of increased education programs, support groups and policy changes aimed at reducing stigma and promoting inclusivity within healthcare settings to improve the health outcomes of HIV-positive children.